Wireless resilience: a LoRa-based sensor network and mobile application for flood victim rescue system - Imran, Mohammad Syameer; Daniel, Muhammad; Attarbashi, Zainab; Handayani, Dini Oktarina Dwi; Iftikhar, Saman; Al-Madani, Dania (IEEE, 2023)
This project aims to help flash floods’ victims and rescuers facilitate rescue efforts. By integrating Internet of Things (IoT) and Global Positioning System (GPS) capabilities, flood victims can use a device (emergency box) that will be activated to send a signal to rescue workers and volunteers to come to the location and rescue them. The box is long lasting, can withstand winds and floats and has a bright light which allows rescuers to locate the victims even in dark or areas with no electricity. Rescuers use a device attached to a signal receiver that receives distress signals from flood victim’s emergency boxes. Then the navigation system will allow rescuers to locate the distress signals. This project has the potential to help rescuers and civilians alike, as this opens new ways to rescue people trapped in flooding by allowing different parties to join the rescue mission easily. The system was evaluated by the success of the rescuer’s device and the mobile application to send and receive respectively the distress signal from the flood’s victim device with accurate location coordinates in different weather conditions, indoor and outdoor, and in both open areas and between buildings. This will be done by taking measures of the power needed for both devices, the covering range between both devices, and the accuracy of the location coordinates.